2012
DOI: 10.1186/1471-2458-12-884
|View full text |Cite
|
Sign up to set email alerts
|

Emergency management in health: key issues and challenges in the UK

Abstract: BackgroundEmergency planning in the UK has grown considerably in recent years, galvanised by the threat of terrorism. However, deficiencies in NHS emergency planning were identified and the evidence-base that underpins it is questionable. Inconsistencies in terminologies and concepts also exist. Different models of emergency management exist internationally but the optimal system is unknown. This study examines the evidence-base and evidence requirements for emergency planning in the UK health context.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…This can be problematic in that outcomes and conclusions may not be generalizable to other populations, settings, exposures or interventions [12][13][14]. Public health in general aims to be informed by the best available evidence and there is an appetite to have more rigorous forms of evidence to inform PHEP practice [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This can be problematic in that outcomes and conclusions may not be generalizable to other populations, settings, exposures or interventions [12][13][14]. Public health in general aims to be informed by the best available evidence and there is an appetite to have more rigorous forms of evidence to inform PHEP practice [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Perry and Lindell (2003) note that 'Emergency management that is not based on accurate knowledge of both the threat and principles of human response is destined to fail' (Perry and Lindell, 2003, p. 59). Several studies covering hazardous events-either natural or man-made-identify risk perception as a factor that may affect the willingness and motivation to implement precautionary behaviours, or to reduce the inherent risks linked to these events (de Zwart et al, 2009;Ho et al, 2008;Lee et al, 2012). Risk perception can also determine the response of individuals and communities to disasters (Howe, 2011).…”
mentioning
confidence: 99%
“…The traditional ‘gold standard’ for research methods (ie, randomised controlled trials) as applied to clinical research is inappropriate and impractical in this field,8 except perhaps in very specific areas (eg, brief psychological intervention for survivors). Usual research practice often requires almost an antithesis to an emergency response situation, that is, it typically requires time for planning and resources for carrying it out at a time when both may be in short supply.…”
Section: Discussionmentioning
confidence: 99%
“…While considerable emphasis has been placed on better planning for disasters, the evidence base for this is questionable particularly within the health sector 8. We have previously reported that the evidence base for health sector emergency planning in high-income countries (HICs), such as the UK, is patchy, not robust and inconsistent 8 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation